Best Paper Selection (Yearbook of Medical Informatics, 2018)
Ancker JS, Edwards A, Nosal S, Hauser D, Mauer E, Kaushal R, with the HITEC Investigators. Effects of workload, work complexity, and repeated alerts on alert fatigue in a clinical decision support system. BMC Med Inform Decis Mak 2017 Apr 10;17(1):36 https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5387195/Blijleven V, Koelemeijer K, Wetzels M, Jaspers M. Workarounds emerging from electronic health record system usage: consequences for patient safety, effectiveness of care, and efficiency of care. JMIR Hum Factors 2017 Oct 5;4(4):e27 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/28982645/Cresswell KM, Mozaffar H, Lee L, Williams R, Sheikh A. Safety risks associated with the lack of integration and interfacing of hospital health information technologies: a qualitative study of hospital electronic prescribing systems in England. BMJ Qual Saf 2017 Jul;26(7):530-41 http://qhc.bmj.com/cgi/pmidlookup?view=long&pmid=27037303Dufendach KR, Koch S, Unertl KM, Lehmann CU. A randomized trial comparing classical participatory design to VandAID, an interactive crowdsourcing platform to facilitate user-centered design. Methods Inf Med 2017 Oct 26;56(5):344-9 http://www.thieme-connect.com/DOI/DOI?10.3414/ME16-01-0098Luna DR, Rizzato Lede DA, Otero CM, Risk MR, González Bernaldo de Quirós F. User-centered design improves the usability of drug-drug interaction alerts: experimental comparison of interfaces. J Biomed Inform 2017 Feb;66:204-13 https://linkinghub.elsevier.com/retrieve/pii/S1532-0464(17)30009-6